Safety, tolerability, pharmacokinetics and effect on serum uric acid of the myeloperoxidase inhibitor AZD4831 in a randomized, placebo‐controlled, phase I study in healthy volunteers. Issue 4 (18th February 2019) - Gan, Li‐Ming; Lagerström‐Fermér, Maria; Ericsson, Hans; Nelander, Karin; Lindstedt, Eva‐Lotte; Michaëlsson, Erik; Kjaer, Magnus; Heijer, Maria; Whatling, Carl; Fuhr, Rainard
Abstract : Aims: Myeloperoxidase activity can contribute to impaired vascular endothelial function and fibrosis in chronic inflammation‐related cardiovascular disease. Here, we investigated the safety, tolerability and pharmacokinetics of the myeloperoxidase inhibitor, AZD4831. Methods: In this randomized, single‐blind, placebo‐controlled, phase I, first‐in‐human study, healthy men in five sequential cohorts were randomized 3:1 to receive a single oral dose of AZD4831 (5, 15, 45, 135 or 405 mg) or placebo, after overnight fasting. After at least 7 days' washout, one cohort additionally received AZD4831 45 mg after a high‐calorie meal. Results: Forty men participated in the study (eight per cohort: AZD4831, n  = 6; placebo, n  = 2). AZD4831 distributed rapidly into plasma, with a half‐life of 38.2–50.0 hours. The area under the plasma concentration–time curve (AUC) increased proportionally with dose (AUC0–∝ slope estimate 1.060; 95% confidence interval [CI] 0.9943, 1.127). Increases in maximum plasma concentration were slightly more than dose proportional (slope estimate 1.201; 95% CI 1.071, 1.332). Food intake reduced AZD4831 absorption rate but did not substantially affect overall exposure or plasma half‐life ( n  = 4). Serum uric acid concentrations decreased by 71.77 (95% CI 29.15, 114.39) and 84.42 (58.90, 109.94) μmol L −1 with AZD4831 135 mg and 405 mg, respectively. Maculopapular rash (moderate intensity) occurred in 4/30 participants receiving AZD4831 (13.3%). No other safety concerns were identified. Conclusions: AZD4831 was generally well tolerated, rapidly absorbed, had a long plasma half‐life and lowered uric acid concentrations after single oral doses in healthy men. These findings support the further clinical development of AZD4831.